25th Meeting of the Brazilian Group of Restorative Dentistry Professors (Brazilian Dental Science, 2023)
Between June 1 st and 3 rd, 2023 the 25 th Meeting of the Brazilian Group of Restorative Dentistry Professors ( was held in the city of Gramado RS After a long period of uncertainty and difficulties, the face to face events were reestablished, confirming one of GBPD's greatest differentials the experience of memorable and traditional moments of reunion, fraternization and welcoming among our members and guests, which filled us with a very latent sense of belonging. In addition, we were given the responsibility and honor of presiding over an exceptional event the celebration of a double Jubilee! 25 meetings forged over 50 years of GBPD history The celebration of such emblematic and remarkable dates allowed us to cherish the past by praising all those who paved the way for us to be where we are today A milestone that deserves to be recorded for posterity. It were three intense days of learning and reflection on the current direction of Dentistry Based on the principles of GBPD, the event brought together science, clinical practice and teaching But we went further, bringing together little discussed, unusual topics in different forms of communication TED was proof of this! We brought together the possibility of technical and scientific improvement in an unprecedented program, with hands on activities and a lot of discussions of high academic standard. The GBPD Meeting which takes place every two years is a unique event because it brings together undergraduate and postgraduate students, specialists and teachers from all over Brazil Dentistry enthusiasts can feel "at home", experiencing lectures, symposia and activities that will certainly make a difference to their professional lives. The Organizing Committee was made up of professors and postgraduate students from various institutions in Rio Grande do Sul and Brazil We would like to thank each and every one of you for all your affection, knowledge, sympathy, patience, commitment, joy and example, culminating in a congress that has already gone down in GBPD history. The 25 th GBPD Meeting was also a milestone in scientific terms we had a record number of submissions, with a total of 142 papers presented, divided into 4 categories (Clinical Case, Teaching, Clinical/Laboratory Research and Scientific Initiation) This is a direct reflection of the serious and hard work carried out within the Higher Education Institutions, which are projecting Brazilian Dentistry to a level of worldwide recognition and importance. The relevance of this production is reflected in the publication of the Meeting’s Proceedings in the Brazilian Dental Science Our most sincere thanks to the journal's editorial board, in the name of its Editor in Chief and also President of the Group, Prof Dr Sérgio Eduardo de Paiva Gonçalves, for publishing this special issue and for all the support given to the 25 th GBPD Meeting.Prof Dr Maria Carolina Guilherme ErhardtProf Dr Thais Thomé FeldensPresidents of the 25 th Meeting of the Brazilian Group of Restorative Dentistry Professors (GBPD)